Manufacturing exports, mining exports and growth: cointegration and causality analysis for Chile (1960 - 2001) - Boriss Siliverstovs; Dierk Herzer (Georg-August-Universität Göttingen, Ibero-America Institute for Economic Research (IAI), 2005)
This study examines the export-led growth hypothesis using annual time series data from Chile in a production function framework. It addresses the problem of specification bias under which previous studies have suffered and focuses on the impact of manufactured and mining exports on productivity growth. In order to investigate if and how manufactured and mining exports affect economic growth via increases in productivity, the study uses Johansen cointegration technique. The estimation results can be interpreted as evidence of productivity-enhancing effects of manufactured exports and of productivity-limiting effects of mining exports.
Keywords: O47; F43; C32; 330; Export-led growth; Chile; cointegration; Export; Industriegüteraußenhandel; Bergbauprodukt; Exportinduziertes Wachstum; Kausalanalyse; Kointegration; Chile